(untitled) (Milan Law Review, 2021)
It is my great pleasure to present to the readers of the Milan Law Review this comparative law symposium by the Younger Comparativist Committee (hereinafter YCC) of the American Society of Comparative Law. Writing this introduction provides to me an opportunity to celebrate two of the most exciting comparative law projects of the last few years.